Vyavasthapan va utpadan niyojan (TYBCom) - Liman M.S., Rawerkar Deepak, Wadekar P.M., Gonda M.G. (Sheth Prakashan, Mumbai, 2004)
Commerce
MARATHI
Keywords: Vyavasthapan va utpadan niyojan (TYBCom); Commerce; Commerce